A Government Policy Implementation and the Potentials of the Public and Private Sectors Towards Development of The Thai-Japanese Creative Muay Thai Tourism Marketing Network - Srimuk, Nattada; Choibamroong, Therdchai (Dusit Thani College Journal, 2020)
The objective of this qualitative research was to analyze a government policy implementation and the potentials of the public and private sectors towards development of the Thai-Japanese creative Muay Thai tourism marketing network. A Semi-structured interview was used as an instrument where in-Depth Interviews were conducted to collect data from 54 key informants related to creative Muay Thai tourism from Thai and Japanese public and private sectors in order to gauge their potential to develop the creative Muay Thai tourism marketing network and administrators in the public sector for the formulation and implementation of the policy. The results of implementing public policy to promote and develop creative Muay Thai tourism marketing network was found to be unsuccessful because; 1. The policies to promote and develop creative Muay Thai tourism marketing network was not concrete, 2. No leader was found to formulate and implement the policy, 3. There was a lack of cooperation between agencies because each agency has its own policy used to perform its task and the leader of collaborative network was not found, 4. There was a lack of policy adoption and implementation among regional agencies. In terms of studying the potential of Thai and Japanese public and private sectors to become a creative Muay Thai tourism marketing network, Tourism Authority of Thailand (TAT) was found to have the potential and readiness to lead the network in terms of coordinating with various agencies, being reliable and acceptable, having marketing potential to promote overall creative Muay Thai tourism and having budget and personnel ready at hand. To develop the Thai-Japanese creative Muay Thai tourism marketing network, it is important to emphasize the formulation of the marketing policy in a more concrete manner. Agencies from all sectors and local organizations need to participate in formulating and developing the policy and setting shared vision. Therefore, to develop the successful the Thai-Japanese creative Muay Thai tourism marketing network, the following network development process must be in place : 1. Identifying the leader, 2. Formulating collaborative policy, 3. Gathering to form the network, 4. Setting shared management, marketing, budget, and personnel goals, 5. Strategic planning, 6. Budgeting, 7. Performing the task as planned, and 8. monitoring and evaluation